2021
DOI: 10.1186/s12862-021-01799-5
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of opsin genes in five species of mirid bugs: duplication of long-wavelength opsins and loss of blue-sensitive opsins

Abstract: BackgroundColor vision and phototactic behavior based on opsins are important for the fitness of insects because of their roles in foraging and mate choice. Related topics, including the duplication and loss of opsin genes, have been well investigated in insect orders such as Coleoptera, Lepidoptera, Hymenoptera, Odonata and Orthoptera, and the findings have been used to develop pest management strategies involving light trapping. Mirid bugs of Hemiptera, which are pests that cause heavy economic losses, show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Among Hemiptera, it has been reported in Acyrthosiphon pisum (22), Aphis craccivora (23), Cimex lectularius (24), Diaphorina citri (25), Nilaparvata lugens (26), and Rhodnius prolixus (27). The family Miridae (Hemiptera: Heteroptera), which includes plant bugs, leaf bugs, or grass bugs, is one of the most diverse families of insects, including over 11,000 species in more than 1,300 genera (4,28). It is the largest family of true bugs belonging to Hemiptera and new members of Miridae are being described constantly.…”
Section: Introductionmentioning
confidence: 99%
“…Among Hemiptera, it has been reported in Acyrthosiphon pisum (22), Aphis craccivora (23), Cimex lectularius (24), Diaphorina citri (25), Nilaparvata lugens (26), and Rhodnius prolixus (27). The family Miridae (Hemiptera: Heteroptera), which includes plant bugs, leaf bugs, or grass bugs, is one of the most diverse families of insects, including over 11,000 species in more than 1,300 genera (4,28). It is the largest family of true bugs belonging to Hemiptera and new members of Miridae are being described constantly.…”
Section: Introductionmentioning
confidence: 99%
“…These differences in reflectance peaks may explain the higher orientation of L. lineolaris toward red than other colors tested in our experiments. A recent study by Xu et al 35 found that mirid bugs have long-wavelength sensitive receptors but have lost the mediumwavelength/blue-sensitive ones, indicating that their visual systems are tuned towards detecting longer wavelengths (red, orange, etc.). However, the reflectance spectra of the traps used in our study show that the yellow and white traps have high reflectance at the longer wavelengths as well as the red traps.…”
Section: Discussionmentioning
confidence: 99%
“…We used RELAX to test for relaxation and intensification of selection on the significant partitions identified by CmC. This method has successfully been applied to test for relaxed selection on opsin genes in several lineages including cichlids, bats, butterflies, and mirid bugs ( Gutierrez et al 2018a , 2018b ; Hauser et al 2021 ; Xu et al 2021 ; Mulhair et al 2023 ). The HYPHY models each automatically inferred gene trees with the GTR model, which were rerooted on Ascaphus truei prior to analyses.…”
Section: Methodsmentioning
confidence: 99%